Exploring Determinants of Consumers' Online Purchasing Behavior for Halal Products in Melbourne - Ridho Jun Prasetyo; Riska Andrilla; Cindy Olivia Pangemanan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study seeks to explore the elements that impact consumers' intentions to purchase halal products online in Melbourne. The variables examined include performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and perceived control. A quantitative research approach was employed to assess the impact of these variables on online purchasing behavior. Data were gathered via a survey questionnaire filled out by 96 residents from the Greater Melbourne region. The findings revealed that four factors—performance expectancy, effort expectancy, social impact, and hedonic motivation—were significant. These key factors can be utilized by businesses as recommendations to attract more customers. In contrast, facilitating conditions and perceived control were found to have no significant impact.